SIGNALS AND SYSTEMS WITH SCILAB (DISCRETE SIGNAL, CONTINUOUS) - Ikhsan Parinduri (Institute of Computer Science (IOCS), 2022)
Presence of the signal can be seen depending on the phenomenon formed is influenced by the time range. In the arithmetic process, the signal can be amplified, weakened, added and multiplied by two signals. In learning digital signal engineering, microprocessors and microcontrollers on signal material and signal formation, it is necessary to have a display in the form of a simulation, this is because it makes it easier for Budi Darma University students to understand and analyze the basic concepts of signals and some discrete and continuous signal formation by using the Scilab application. The purpose of this study is to make it easier to provide an explanation for learning about signal concepts in the form of simulations. Research Stages The basic concept of signal, signal explanation, Program Code Input and Simulation with Program Applications.